Pengaruh Kualitas Pelayanan, Kepercayaan dan Kepuasan Nasabah Terhadap Loyalitas Nasabah PT. Bravo Engineering Batam - Carissa Alverina; Triana Ananda Rustam (Komunitas Dosen Indonesia, 2022)
Companies must pay attention to customers demand for the services offering. Company may following the desired also need of customers which were always change, creating producted design to meeting that are need and continuously study the possible benefits that will be obtained from the services provided. The ultimate goal of the steps taken by the company is to create improvements in service quality, trust, and customer satisfaction so this many customers remainng loyals to the good and services offering by the company. That studies aims to determining the effects of service quality, trust, and customer satisfaction on customer loyalty at PT Bravo Engineering Batam. That researches designed using researches designed and quantitatives researches methods. Data collections technique by distributed questionnaires to 123 respondents, namely customers of PT Bravo Engineering Batam. The results of these studies indicated that service quality (X1), trust (X2), and customer satisfaction (X3) partially and simultaneously has a significants effects on customer loyalty (Y). The resulting of the coefficients of determinations tests showed these service quality (X1), trust (X2), and customer satisfaction (X3) affect customer loyalty (Y). by 93.3 percents, while the rests is influence by other variables not examining in these studies.